2016
DOI: 10.1113/jp271403
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and gastrointestinal sensory function: altered colonic mechanosensory and chemosensory function in the aged mouse

Abstract: Key points Remarkably little is known about how age affects the sensory signalling pathways in the gastrointestinal tract despite age‐related gastrointestinal dysfunction being a prime cause of morbidity amongst the elderly populationHigh‐threshold gastrointestinal sensory nerves play a key role in signalling distressing information from the gut to the brain.We found that ageing is associated with attenuated high‐threshold afferent mechanosensitivity in the murine colon, and associated loss of TRPV1 channel fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
(84 reference statements)
2
26
0
2
Order By: Relevance
“…In a recent study from our laboratory the effect of aging on mouse afferent nerve sensitivity was measured. We found that aging correlated with a reduction in sensory firing and altered serotonergic signaling . A similar decline in afferent sensitivity was also observed for the human bowel although sample size was limited by the availability of tissue.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In a recent study from our laboratory the effect of aging on mouse afferent nerve sensitivity was measured. We found that aging correlated with a reduction in sensory firing and altered serotonergic signaling . A similar decline in afferent sensitivity was also observed for the human bowel although sample size was limited by the availability of tissue.…”
Section: Discussionsupporting
confidence: 76%
“…Experimental studies with rodents have shown that the numbers of myenteric and submucosal neurones decline with age, and that sympathetic innervation and vagal nerves deteriorate . A recent study from our laboratory found that mechanosensation and serotonergic chemosensitvity in the mouse intestine was significantly inhibited with age . However, there are currently no equivalent human data showing how aging affects sensory signaling from the bowel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the gastrointestinal tract contains intrinsic and extrinsic enteric neurons, smooth muscle cells, and interstitial cells of Cajal (ICC), which respond to mechanical deformations by altering transmembrane ionic currents in a process called mechanoelectrical coupling . It has been demonstrated that factors such as aging and diabetes change the mechanosensitivity. Furthermore, it has been reported that enteric neurons were affected by malnutrition .…”
Section: Discussionmentioning
confidence: 99%
“…Ageing is also associated with changes in sensory function, which is highlighted here in relation to mechanosensory and chemosensory function in the gut (Keating et al . ) that contribute to gastrointestinal dysfunction and morbidity.…”
mentioning
confidence: 99%